MEASURES OF CONCENTRATION LEVEL IN THE BANKING SECTOR: EMPIRICAL EVIDENCE FROM SERBIA, CROATIA AND MONTENEGRO - Kaličanin, Tijana; Terzić, Ivica (The European Journal of Applied Economics, 2023)
In the last few years there were significant changes in financial sector on the global level. The aim of this paper is to analyze banking sectors and make comparative analysis between Serbia, Montenegro and Croatia, having in mind that the banking sector takes the biggest part of financial sector in these countries. The covered period of the analysis is 2017-2021 and selected ratios of concentration were calculated to define market structures in these countries. Market changes are also reflected in the reduction in the number of banks due to mergers and acquisitions in the last few years. The results of the static and dynamic analysis of concentration indicate that Serbia banking sector is slightly less concentrated that Croatia and Montenegro banking sector. The decrease in the number of the banks had significant impact on market structure and it will attract attention to further research.